Deconstructing the Board of Peace: A political Marxist and post-colonial analysis - Siti Mawaddah Palamani; Satya Wira Wicaksana (Privietlab, 2026)
This study examines the Board of Peace (BoP) as a structural embodiment of global capital mandates expressed via the discourse of rebuilding and stabilization. Employing Political Marxism from Benno Teschke's critique of international order and its social property relations alongside Mignolo and Quijano's Coloniality of Power, Poets' Pacification Paradigm, and Mandelkern's Neoliberal Depoliticization framework, this study argues that BoP constitutes a new imperial instrument disguised as a peace institution. Analysis of primary documents such as UNSC Resolution 2803, BoP Charter, and international legal critiques, reveals critical anomalies: the charter's absence of any reference to Gaza or Palestinian self-determination; authority concentrated in a single individual without accountability mechanisms; and an economic reconstruction blueprint resembling a market-opening scheme for transnational capital rather than a people-centered recovery program. BoP ultimately represents a codification of existing power relations rather than a genuine multilateral institution. Keywords: Board of Peace, Political Marxism, New Imperialism, Pacification, Depoliticization